2021
DOI: 10.3390/polym13111873
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Clinical Performance of the Fast-Modelling Bulk Technique and Composite-Up Layering Technique in Class I Cavities

Abstract: The aim of this study was to assess the one year clinical performance of a new application method, the Fast-Modelling Bulk Technique (FMBT), in comparison to the Composite-Up Layering Technique (CULT) in posterior cavities. Thirty patients with two class I cavities on permanent human molars were enrolled in the present study. A total of sixty class I cavities were prepared and randomly divided according to the restoration technique used: 30 cavities restored by incremental layering technique and modelling of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Overall, bias risk for all domains was low for two studies 32 , 33 (11.1%). Two studies 34 , 35 demonstrated high risk (11.1%); and fourteen studies 6 , 36 48 showed some concerns (77.8%) for overall bias risk as shown in Figs. 2 and 3 .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, bias risk for all domains was low for two studies 32 , 33 (11.1%). Two studies 34 , 35 demonstrated high risk (11.1%); and fourteen studies 6 , 36 48 showed some concerns (77.8%) for overall bias risk as shown in Figs. 2 and 3 .…”
Section: Resultsmentioning
confidence: 96%
“… Study Type of Teeth and Restoration Groups Teeth Per Group Etching Method Adhesive System Resin Placement Technique Salem et al, 2022 36 Molar Bulk Resin + Conventional Resin 18 Ultra-Etch selective enamel etching and rinsing G-premio Bond EverX posterior + G-ænial Sculpt Two-step Bulk (Class II) Conventional Resin 18 G-ænial Sculpt Incremental Endo Hoshino et al, 2022 34 Premolar (94) and Molar (65) Bulk Resin + Conventional Resin 53 35% phosphoric acid gel (Ultra-etch) etching and rinsing Adper Single Bond 2 Filtek Bulk Fill Flow + Filtek Z350XT Two-step Bulk (Class II) Bulk Resin + Conventional Resin 53 XP Bond2 SureFil SDR + TPH3 Two-step Bulk Conventional Resin 53 Peak Universal Amelogen Plus Incremental Sekundo et al, 2022 37 Premolar (56) and Molar (64) Bulk resin 60 35% phosphoric acid (Scotchbond Universal Etchant) selective enamel etching and rinsing 3M Scotchbond Universal adhesive Filtek Bulk Fill Posterior Bulk (Class II) Conventional resin 60 Filtek Supreme XTE Incremental Hardan et al, 2021 6 Premolar and Molar Bulk resin 30 32% phosphoric acid gel (Scotchbond universal) etching and rinsing Two-step etch-and-rinse Adper Single Bond Filtek bulk-fill Posterior Restorative Bulk (Class I) Conventional resin 30 Filtek Z250XT Incremental ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct resin composite restorations are most preferred by patients as adequate not only for anterior teeth, but also for posterior teeth. The use of this kind of restoration has increased and a lot of improvements in resin materials formulations and clinical techniques have been developed in recent years [ 1 , 2 ]. Despite this, the performing of large restorations including the proximal region presents challenges for direct resin composite restorations, such as the recovery of an adequate proximal contacts, anatomical form, wear resistance, and marginal adaptation [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most resin composite materials require a 20 s light-curing time period based on the use of a well-conditioned light source, mean light irradiation of 1000 mW/cm 2 from an 8 to 10 mm diameter light guide tip to adequately polymerize resin component increments with thicknesses from 1.5 to 2 mm [2,12]. Conversely, bulk-fill resin composites, which allow bulk filling to the deep cavity, have been introduced as a useful restorative material that can be applied in thick layers (thicknesses up to 4 mm), and save chair-time in comparison with previous incremental techniques [2,[16][17][18]. Clarifications regarding the actual bonding states of direct resin composite restorations with single-or bi-resin restoratives after cyclic loading simulating the intra-oral environment will contribute to the determination of the appropriate restoration methods in clinical practice.…”
Section: Introductionmentioning
confidence: 99%